(untitled) (Journal of Economic Research & Business Administration, 2015)
This article describes the influence of oil prices on the fuel market in Kazakhstan and the current state of the fuel market. For Kazakhstan crude oil production is profitable due to high oil prices, and as a result the production of motor fuel remains at a low level. And it was also considered the relationship between the price of gasoline in Kazakhstan, the index of consumer prices and world prices for oil. Comparing the dynamics of price changes can be ascertained that the relationship between these parameters is not always positive. Correlation analysis showed that the relationship between these indicators are weak. Also in the article provided a comparative analysis of gasoline prices in Kazakhstan and other countries of the world. It can be said that the presence of crude oil in the country is not the most important factor in pricing of gasoline, and government policies in the fuel market is important